The Analysis of the Ownership Structure and Efficiency of Chinese City Commercial Banks - Dong, Yuan (2017)
This dissertation aims to investigate the ownership structure and efficiency of Chinese city commercial banks and supply reference for the improvement of ownership structure. Based on the theoretical analysis of the relationship between ownership structure and the efficiency of city commercial banks, this dissertation uses the data of 29 Chinese city commercial banks during the period from 2014 to 2016 to make an empirical study on the relationship between the ownership structure and efficiency. SFA is used to measure the efficiency. The results show that the introduction of foreign investor benefits the improvement of efficiency. In addition, the ownership concentration is positively related to efficiency while the holding capacity of the largest shareholder has negative impact on efficiency.